Beyond Advertising Narratives: “Josefinas” and their storytelling products - Liliana Dias; Patrícia Dias (Anàlisi: Quaderns de Comunicació i Cultura, 2018)
In the last few years, advertising narratives have become increasingly important. Facing an environment of fierce competition and communication overload, brands needed to reinvent their communication strategies, and stories became protagonists, particularly in the digital environment.